Differential Interaction of Peripheral Blood Lymphocyte Counts (ALC) With Different in vivo Depletion Strategies in Predicting Outcomes of Allogeneic Transplant: An International 2 Center Experience - Sheth, Vipul; Kennedy, Vanessa; de Lavallade, Hugues; Mclornan, Donal; Potter, Victoria; Engelhardt, Brian G.; Savani, Bipin; Chinratanalab, Wichai; Goodman, Stacey; Greer, John; Kassim, Adetola; York, Sally; et al. (Frontiers in Oncology, 2019)
Dosing regimens for antithymocyte globulin (ATG) and anti-CD52 antibody (alemtuzumab) for graft vs host disease prophylaxis (GVHD) are empiric or weight-based, and do not account for individual patient factors. Recently, it has been shown that recipient peripheral blood absolute lymphocyte count (ALC) on the day of ATG administration interacts with the dose of ATG administered to predict transplantation outcome. Similarly, we wanted to analyze if the recipient ALC interacts with alemtuzumab dosing to predict outcomes. We retrospectively compared 364 patients, 124 patients receiving ATG (anti-thymocyte globulin) for GVHD prophylaxis, and undergoing unrelated first allogeneic transplant for myeloid and lymphoid malignancies (group 1) to 240 patients receiving alemtuzumab (group 2), in similar time period. There was no difference in survival or acute and chronic GVHD between 60mg and 100mg of alemtuzumab dosing. Unlike ATG (where the pre-transplant recipient ALC interacted with ATG dose on day of its administration (day 1) to predict OS and DFS, (p=0.05), within alemtuzumab group, the recipient ALC on second day of alemtuzumab administration (day 2) and its interaction with alemtuzumab dose strongly predicted OS, DFS and relapse, (p=0.05, HR- 1.81, 1.1-3.3; p=0.002, HR-2.41, CI, 1.3-4.2; and p=0.003, HR-2.78, CI, 1.4-5.2), respectively. ALC (day 2) of 0.08 x 109/lit or higher, had a specificity of 96% in predicting inferior DFS. Like ATG, there is definite but differential interaction between the recipient peripheral blood ALC and alemtuzumab dose to predict OS, DFS, and relapses.